A rare case of mammary hamartoma presenting as malignant on radiological assessment and benign on pathological examination: a case report - Yang, Qingfeng; Gong, Yiping; Hu, Jin (Frontiers in Oncology, 2025)
Breast hamartomas are rare, benign, and encapsulated lesions composed of a combination of fatty, glandular, muscular, and fibrous tissue. Mammography provides an overview of the breast’s structure and can identify the characteristic “breast within a breast” appearance typical of hamartomas. Ultrasound is useful for determining the echogenicity and vascularization of hamartomas, thereby helping to differentiate them from potential malignancies. Magnetic Resonance Imaging (MRI) is another indispensable tool in the diagnostic arsenal for breast hamartomas. One of the major challenges in differential diagnosis is distinguishing hamartomas from fibroadenomas, which typically occur in young women. Here, we present a case of a 21-year-old female with a highly suspicious lesion based on radiological features, which was ultimately diagnosed histologically as a breast hamartoma.